Fracture load of different veneered and implant-supported 4-UNIT cantilever PEEK fixed dental prostheses. (May 2022) - Micovic Soldatovic, Danka; Liebermann, Anja; Huth, Karin C.; Stawarczyk, Bogna
Abstract: Objectives: To determine the fracture load before and after artificial aging of implant-supported 4-unit cantilever fixed dental prostheses (FDP) with frameworks made of two differently filled polyetheretherketone (PEEK) compounds and veneered using three different techniques. Methods: A total of 120 duplicate 4-unit FDP frameworks were produced (n = 60 milled from PEEK, 20% TiO2 filled and n = 60 pressed from PEEK, 30% TiO2 filled) and veneered using three different techniques: (i) digital veneerings, (ii) conventional resin composite veneerings and (iii) prefabricated veneers (n = 20 per subgroup). The FDPs were adhesively bonded to titanium abutments and the fracture load was measured in a universal testing machine (1 mm/min) before and after artificial aging in a mastication simulator (1, 200, 000 cycles, 50 N, TC: 5/55 °C, 6000 cycles). The fracture patterns were analyzed using digital microscopy. Data were analyzed using the Kolmogorov-Smirnov test, two-way ANOVA, post hoc Scheffé, Chi 2 -test ( p < 0.05 ), and Weibull modulus m, as well as fracture patterns using the Ciba-Geigy table. Results: Veneering technique and filler content significantly affected the fracture load ( p < 0.001 ). Prefabricated veneers showed higher fracture load ( p ≤ 0.001 ) whereas digital and conventional veneerings were similar ( p = 0.451 ). PEEK with 30% filler content presented higher fracture load ( p < 0.001 ) compared with PEEK with 20%. Aging showed no effect on fracture load ( p = 0.176 ). Regarding fracture types, no significant differences were found among the groups ( p = 0.055 ). Conclusions: Filler content of PEEK compound as well as veneering technique influenced fracture load while aging had no effect on fracture load. FDPs made of PEEK with 30% of filler content veneered using prefabricated veneers had the highest fracture resistance. Graphical abstract: Image 1 Highlights: Aging showed no effect on mechanical properties of implant-supported 4-unit cantilever FDPs. All examined FDPs exhibited higher fracture load values than the reported maximum occlusal forces in the posterior region. Veneering method highly influenced long-term stability of veneered and implant-supported PEEK FDPs.